Electricity consumption and sectoral output in Uganda: An empirical investigation - Joseph Mawejje; Dorothy N. Mawejje (Journal of Economic Structures, 2016)
We examine the causal relationship between electricity consumption and sectoral output growth in Uganda. First, we use vector error correction techniques to estimate the long-run relationship between electricity consumption and GDP growth. Second, we apply Granger causality tests to determine the direction of this relationship. Third, we disaggregate GDP into its major sectors of agriculture, industry and services and test for Granger causality between sectoral output growth and electricity consumption. At the macro-level, results suggest long-run unidirectional causality running from electricity consumption to GDP. At the sectoral level, results indicate long-run causality running from electricity consumption to industry; a unidirectional short-run causality running from services sector to electricity consumption; and neutrality in the agricultural sector. These results have important implications for policy. In particular, policies that improve electricity generation and consumption will accelerate growth in Uganda by facilitating industrial sector growth. Moreover, electricity conservation policies can be applied in the services sector without hurting growth.
Keywords: Q41; Q43; 330; Electricity consumption; Sectoral output; Uganda